Socio-Demographic Predictors of Psychological Distress among Female School Teachers: Role of Age, Education and Socio-Economic Status - Akhlaq, Bisma; Khan, Aqeel Ahmad (Annals of Human and Social Sciences, 2025)
This study was carried out to address the socio-demographic predictors of psychological distress among female school teachers. This is an acknowledged fact that psychological distress among teachers is manifested in various ways, affecting their emotional, cognitive, and physical well-being. That is why, understanding these common socio-demographic predictors of psychoplogical distress are important for identifying and addressing the mental health challenges faced by the teachers. To explore the socio-demographic predictors a sample of 176 female teachers was recruited by using multistage sampling method. The level of psychological distress was measured by using Kessler Psychological Distress Scale (K10). This was a quantitative research and the cross-sectional research design was used. The collected data was analysed by using SPSS. The findings from the results revealed that age, education and socio-economic status were significant socio-demographic correlates of psychological distress among the female teachers. Furthermore, the level of psychological distress was higher among younger teachers, doctors and among those having high or middle socio-economic status. On the basis of the findings of this study it recommended that socio-demographic correlates are t also contribute to the level of psychological distress among teachers. Hence, there is a dire need to address these socio-demographic correlates to decrease the teacher’s psychological distress.